The Legal Power of Executorial Title in a Notary's Deed Concerning Debt Recognition in Banking Practice - Situmorang, Linda Vera Uli; Sitompul, Roswita; Isnainul, OK (IJBLE Scientific Publications Community Inc., 2025)
This research is motivated by the use of notarial deeds in banking practice because notarial deeds have the position of authentic deeds. One form of using a notarial deed in banking practice is the use of a notarial deed in the form of a debt acknowledgment deed. The legal research method used in this research is normative juridical research which is research carried out or aimed only at written regulations with the nature of descriptive analysis research which is a method that functions to describe or provide an overview of the object being studied. The data source used is secondary data with quantitative data analysis. The results of this research are that the legal strength of the executorial title in the debt acknowledgment deed aligns the debt acknowledgment deed with the court decision. The executorial title or irah-irah gives the authority to carry out executions without having to go through a court decision, but the execution is carried out by asking for court assistance or what is called fiat execution. With the existence of an executorial title which aligns the debt acknowledgment deed with a court decision that has legal force permanent (inkarcht van gewidje), the authority of the notary in including the executive title in the debt acknowledgment deed is regulated in Article 57 UUJN, the person with the authority to issue the grosse deed is the notary. The implementation of Executorial Title in Banking Practice is carried out on Debtors who are in default and cannot fulfill their obligations to pay debts according to the time period agreed in the credit agreement and become bad debts, then the bank as creditor has the right to recover its receivables by carrying out fiat execution on collateral objects that have been encumbered with mortgage rights.